1982
DOI: 10.1016/s0007-0912(17)46813-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Midazolam as an Induction Agent: Comparison With Thiopentone

Abstract: A prospective, randomized, single-blind investigation was undertaken into the value of midazolam as an agent for the induction of anaesthesia. Sixty patients undergoing orthopaedic surgery of short duration were allocated randomly to receive either midazolam 0.2 mg kg-1 or thiopentone 3 mg kg-1. The induction time (measured as the time until loss of eyelash reflex) in the thiopentone group was significantly shorter than in the midazolam group. No differences were observed between the two drugs as regards time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
2

Year Published

1983
1983
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 5 publications
0
8
1
2
Order By: Relevance
“…The incidence was much less in midazolam and in co-induction group. The incidence of midazolam-induced apnoea in literature is more than we observed (18 to 78%) 12 .…”
Section: Discussioncontrasting
confidence: 46%
“…The incidence was much less in midazolam and in co-induction group. The incidence of midazolam-induced apnoea in literature is more than we observed (18 to 78%) 12 .…”
Section: Discussioncontrasting
confidence: 46%
“…Arterial blood pressure and systemic vascular resistance increased after 3 min following thiopentone administration and decreased following midazolam administration 156 [II]. On the other hand, no differences in arterial blood pressure and heart rate, 157 stroke volume, cardiac output or systemic vascular resistance 158 were demonstrated in these studies [II]. Table 8 Recommendations for hypnotic drugs considering the haemodynamic system.…”
Section: Thiopentone and Midazolammentioning
confidence: 99%
“…16 Nevertheless, the use of midazolam has produced haemodynamically stable anaesthesia in patients for heart surgeryl7 and in healthy subjects. 18 In our investigation, the QF interval remained constant during the induction of anaesthesia, an indication that ventricular performance was unaffected by either drug at the concentrations used. Apparently, the benzodiazepines produced little cardiac depression in the sick patients in our study which supports previous work which showed that systolic time intervals do not change during anaesthetic induction with midazolam in a healthy population.…”
Section: Discussionmentioning
confidence: 48%